KORELASI MENGAJAR DAN MEDIA TERHADAP MENULIS NARASI SISWA KELAS V SDN 20 PONTIANAK - Anggraeni, Dewi Putri; Syam, Christanto; Salem, Laurensius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractIndonesian language learning includes four language skills: listening, speaking, reading and writing skills. Essentially the main function of language is as a communication tool. Therefore, Indonesian language and literature learning is directed to enable students to communicate, both oral and written. This research was based on the facts in the field that show the learning result of writing the narrative paragraph on the students of class V in SD Negeri 20 Pontianak Semester 1 of the lesson year 2013/2014 no correlation was expected. The result of the research shows that there is a significant correlation between the ability of the teaching teacher, the picture story media to the result of learning to write the narrative of the students of class V SDN 20 Pontianak Semester 1 of the lesson year 2013/2014. Based on the data processing and analysis, it can be concluded that: There is a correlation between teacher's teaching ability, picture story media, and student learning outcomes in Indonesian language subjects at SDN 20 Pontianak. After seeing the results of questionnaire answers, observations and interviews the authors suggest that: Indonesian teachers should be able to, explain, help, accept and address the positive and negative things that exist in the learnersÂ Keywords: pictorial story media, teacher's teaching ability and writing narrative